2023
DOI: 10.3389/fpsyg.2022.1081372
|View full text |Cite
|
Sign up to set email alerts
|

How does interactive virtual reality enhance learning outcomes via emotional experiences? A structural equation modeling approach

Abstract: IntroductionInterest in interactive virtual reality (IVR) is increasing due to its potential for embodied learning and group-led teaching. However, few studies have investigated the internal mechanism by which IVR technology features and learning experiences affect learning outcomes in terms of psychological and emotional value. Based on media technology models and the control value theory of achievement emotions (CVTAE), this study uses structural equation modeling (SEM) to investigate the correlations among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 69 publications
(128 reference statements)
0
6
0
Order By: Relevance
“…Virtual reality (VR) enhances interactive learning experiences by promoting engagement, autonomy, creativity, and metacognition (Yang et al, 2023); (Zaen & Mardiani, 2018); (Essoe et al, 2022). VR technology facilitates a shift from traditional teaching methods to immersive, threedimensional learning environments, fostering situational and contextual learning.…”
Section: Resultsmentioning
confidence: 99%
“…Virtual reality (VR) enhances interactive learning experiences by promoting engagement, autonomy, creativity, and metacognition (Yang et al, 2023); (Zaen & Mardiani, 2018); (Essoe et al, 2022). VR technology facilitates a shift from traditional teaching methods to immersive, threedimensional learning environments, fostering situational and contextual learning.…”
Section: Resultsmentioning
confidence: 99%
“…31 Therefore, the MR functions that this study mainly focuses on are the system's response time to the user's hand operations and the fidelity of the combination of the model and the real environment. 33 Good satisfaction is considered to directly trigger the willingness to actively learn. 34 However, subsequent research found that users' satisfaction with the system does not completely mediate the user's behavioral intention.…”
Section: Mr Featuresmentioning
confidence: 99%
“…The emotional goals encompass learners' sentiments, emotions, and appreciation of the value of learning, 32 the learning outcomes of interest in this study center around affective goals. The learning outcome variables used by Yang et al when studying emotional goals include learning satisfaction and perceived learning effect 33 . Good satisfaction is considered to directly trigger the willingness to actively learn 34 .…”
Section: Theoretical Foundation and Technical Pathwaymentioning
confidence: 99%
“…Presence can be seen as the sense of being there or being in one place [50]. In the literature on VR experiences, the concept of presence is also tackled as spatial presence, which can be defined as the "cognitive perception that a person's body is occupying a space in which they feel in sync with the actions of the virtual experience" ( [51], p. 2).…”
Section: Presencementioning
confidence: 99%